Tissue-invasive CMV disease is associated with poor prognosis during remission induction therapy for autoimmune inflammatory rheumatic diseases - Oka, Hideki; Sumitomo, Shuji; Miyakoshi, Chisato; Ohmura, Koichiro (Frontiers in Immunology, 2026)
ObjectivesCytomegalovirus (CMV) is a notable health concern in immunocompromised individuals and presents as CMV reactivation (CMV infection) or CMV reactivation with tissue invasion (CMV disease). However, few studies have distinguished these CMV patterns during induction therapy for autoimmune inflammatory rheumatic diseases (AIIRDs). This study investigated the clinical characteristics of patients with CMV disease, diagnosed through histopathology, immunohistochemistry, or polymerase chain reaction, during induction therapy for AIIRDs in comparison with those of patients with CMV infection.MethodsThis single-center retrospective study included patients with AIIRDs undergoing remission induction therapy with glucocorticoids ≥20 mg/day for ≥4 weeks, hospitalized between 2013 and 2024. Data on clinical characteristics, treatments, and outcomes were collected, and CMV disease, determined by histopathological findings, was compared with CMV infection.ResultsAmong 82 patients administered AIIRDs and positive for CMV antigenemia, 14 had CMV disease and 68 had CMV infection. CMV disease was associated with lower platelet counts, higher aspartate aminotransferase/alanine transaminase levels, and higher maximum antigenemia. The prevalence of coincident infections (93% vs. 32%) and mortality rate (57% vs. 24%) were higher in patients with CMV disease. Kaplan–Meier analysis showed poorer survival for patients with CMV disease (log-rank test, p=0.027). Receiver operating characteristic analysis identified antigen count (cutoff: 36) as the best predictor of CMV disease.ConclusionCMV disease during remission induction therapy for AIIRDs is associated with higher antigenemia, more coincident infections, and poorer survival compared with CMV infection. Identifying the risk factors for CMV disease, including antigenemia and coincident infections, can improve patient outcomes.